The Influence of E-Service Quality on Patient Satisfaction and Loyalty in Hospitals: A Systematic Literature Review Using the PRISMA Framework in 2020-2025 - Leny Widio Wati; Anton Agus Setyawan; Siti Soekiswati (Indonesian Health Issue, 2026)
Background: The advancement of digital technology in the healthcare sector has driven hospitals to improve the quality of electronic services (e-service quality) in meeting patients’ expectations for convenience, speed, and service effectiveness. Objective: This study aims to analyze the influence of e-service quality on patient satisfaction and loyalty in hospitals. Methods: This research employed a Systematic Literature Review guided by the PRISMA framework and conducted in October 2025. Articles were collected from the ScienceDirect, PubMed, ProQuest, and Google Scholar databases, yielding a total of 14,273 articles, which were screened and filtered into eight relevant studies that met the inclusion criteria. Results: E-service quality has a significant effect on patient satisfaction through four factors: integrated digital services, emotional and trust dimensions, technical quality and user experience, and ease of use. Furthermore, patient loyalty is formed through two mechanisms improvement of electronic service quality and technological integration that encourages revisit intention. Conclusion: E-service quality plays an important role in enhancing patient satisfaction and loyalty in hospitals.